Cystic fibrosis screening: a fetus with hyperechogenic bowel may be the index case. Issue 8 (August 1998) - Muller, F; Dommergues, M; Simon-Bouy, B; Ferec, C; Oury, J F; Aubry, M C; Bessis, R; Vuillard, E; Denamur, E; Bienvenu, T; Serre, J L
Abstract : BACKGROUND: The potential of hyperechogenic fetal bowel to act as a hallmark for prenatal cystic fibrosis screening in the general population is controversial. METHODS: Our goal was to evaluate the incidence of cystic fibrosis in 209 fetuses with hyperechogenic bowel diagnosed at routine ultrasonography and with no family history of cystic fibrosis. The diagnosis of cystic fibrosis was based on prenatal screening for the eight mutations most frequently observed in France (deltaF508, deltaI507, 1717-1G-->A, G542X, G551D, R553X, W1282X, N1303K) and at postnatal follow up. RESULTS: The overall incidence of cystic fibrosis was 7/209 (3.3%) which is 84 times the estimated risk of CF in the general population (112500). Of these seven cases, six were diagnosed prenatally based on DNA analysis (deltaF508/deltaF508, n=5; deltaF508/G542X, n=1). One case in which only one mutation had been recognised was diagnosed clinically after birth (deltaF508/unidentified mutation). Of the seven cases, none was diagnosed at 16-19 weeks, four at 16-24 weeks, and three after this. The incidence of heterozygous fetuses (15/209, 7%) was not significantly higher than the 5% expected in the general population. The mutations involved in these heterozygous cases were deltaF508 (n=13), G542X (n=1), and G551D (n=1). CONCLUSIONS: Screening for cystic fibrosis should be offered to families in which fetal hyperechogenic bowel is diagnosed at routine ultrasonography. This underlines the need to review genetic counselling in this situation where the fetus is the index case for a genetic disease.